Financial Performance Analysis of Conventional Banks and Sharia Bank in PT. Bank Panin Tbk. and PT. Bank Panin Syariah Tbk - Nurhadi N, Muhammad; Putra, Angwal Jaya (Universitas Patria Artha, 2017)
This study aims to analyze the differences in financial performance of PT. Bank Panin Tbk. And PT. Bank Panin Dubai Syariah Tbk. The period 2013 - 2015.This research uses descriptive qualitative analysis method by using LDR / FDR ratio, NPL / NPF, BOPO / OER, ROA, ROE and KPMM to see difference of financial performance of both Bank.Based on the results of the analysis and discussion can be concluded that the level of Liquidity Bank Panin Tbk. Healthier than Bank Panin Dubai Syariah Tbk. While Asset Quality of Bank Panin Tbk. Healthier than Bank Panin Dubai Syariah Tbk. In addition, the efficiency level of both banks is in good condition. The level of profitability is seen from the Bank's second ROA ratio in unhealthy condition, while seen from the ratio of ROE only Bank Panin Tbk. Who are in good health. The capital level of both banks is in good condition